PERANCANGAN WEBSITE AROMA KITCHEN (FAMILY RESTAURANT & GRILL) DI KOTA PADANG - LAURA SRIUTAMI JUNENSA, Hendra Afriwan, S.Sn., M.Sn., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Aroma Kitchen (Family Restaurant & Grill) is a restaurant which provides a fairly complete menu with the concept of family restaurant (family restaurant) located in the city of Padang. Location located at JL. Prof. Dr. Hamka No. 44-45 Tabing Padang. To face competition in the corporate world, the Aroma Kitchen (Family Restaurant & Grill) want to try creating good services as well as different flavors with other businesses in the hope of being able to satisfy existing customers and attract new customers. The purpose of the design of this website is to provide information to the public about Aroma Kitchen (Family Restaurant & Grill) to be more known and can increase the value in the region field, moreover as an effective promotional and media can cover the whole world through online media which can be accessed at any time.The design of this website is done through several stages, namely data collection, data analysis and design. The process of data collection through interviews with owners and employees of Aroma Kitchen (Family Restaurant & Grill), observation and documentation. While the process of analysis of the data using analysis S.W.O. T analysis: Strength (strength), Weakness (Weakness), Opportunities (Opportunity), Threats (Threats).The result of designing websites are 1366 x 768 pixels, showing 5 dish menu, namely: home (home), about (about), menu, gallery (Gallery), contact us (contact) in the Indonesian Language and the language of the United Kingdom.The result of designing this website consists of the major media outlets (prime media) and supporting media (supporting media). Major media Websites, while media advocates in the form of Web banners, posters, Paper Bag, X-Banner, t-shirts, Totebag, Flag chain and Mug.Key Words: Aroma Kitchen (Family Restaurant & Grill), Website, Design